Optimizing Healthy Movement Through Gymnastics and Consumption of Healthy Food For Odgj at UPTD Liposos - Sugiyanto, Meirizka Maulidya; Nisa, Khoirun; Dewantika, Aisyah; Dei, Putri Safina; Primastuti, Amanda Marlita; Nisa, Vara Choirun; Hadiyanto, Agus; Zahira, Zivana Zalfa; Y, Cicinda Nur Mufida; Ririanty, Mury (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to optimize the Healthy Living Community Movement (GERMAS) among People with Mental Disorders (ODGJ) at UPTD Liposos Jember through gymnastics and healthy eating. It addresses Indonesia’s triple burden of disease, emphasizing mental health as a key non-communicable disease, and promotes holistic recovery through physical activity and nutrition. Method: A community service design was used, involving 49 participants (29 students, 20 ODGJ). Activities followed three stages: orientation, implementation (joint gymnastics and education on healthy food), and evaluation via sharing sessions. The approach was guided by Community-Based Participatory Research (CBPR). Practical Applications: The intervention enhances physical and mental health, social interaction, and health awareness. It can be replicated in rehabilitation centers to reduce stigma and improve quality of life. Conclusion: The GERMAS-based activity successfully boosted enthusiasm, well-being, and social engagement, demonstrating its value in mental health promotion and sustainable behavior change.